Ciència i subjectivitat en la poesia d’Àngel Terron - Pons, Margalida (Studia Romanica Posnaniensia, 2016)
The relationships between science and poetry are usually examined from three perspectives: the lexicon (the use of scientific vocabulary in poems), the topical point of view (the presence of scientific motifs) and the subjective/authorial bias (the consideration that the fact of the author being a scientist confers scientificity to his literary texts). This article aims to deviate from the examination of the parallels between poetry and science to concentrate on the study of the intersections: in particular, the ways in which science and poetry deal with a) the process of symbolization, b) the development of procedures and c) the idea of creative disorder. The writing of the poet and chemist Angel Terron will be the testing ground for these investigations.